2022
DOI: 10.1007/s00432-022-04513-0
|View full text |Cite
|
Sign up to set email alerts
|

The negative impact of opioids on cancer patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis

Abstract: BackgroundAs one of the most effective analgesics, opioids are essential for patients with cancer-related pain, even in the context of the opioid abuse crisis. The current meta-analysis aimed to identify whether concomitant exposure to opioids can affect the e cacy of ICIs and lead to a worse prognosis. MethodsPubMed, Embase, and the Cochrane Library were searched Based on the PRISMA checklist, through April 2022, for the following terms: ("opioids" OR "concomitant medication") AND ("Neoplasm" OR "Carcinoma" O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Our findings reveal a noteworthy association between OA treatment and significantly reduced PFS and OS in cancer patients receiving ICI therapy. Consistent with previous research hinting at the potential negative influence of opioids, our results highlight that the impact of opioids varies by tumor type, suggesting a need for tumor-specific strategies in clinical practice [ 6 9 ]. The relationship between an ECOG PS of 1 or higher and reduced OS, elevated LDH levels above the normal range, and reduced PFS and OS suggests an association between increasing disease burden and OA usage, which may be related to a worse prognosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings reveal a noteworthy association between OA treatment and significantly reduced PFS and OS in cancer patients receiving ICI therapy. Consistent with previous research hinting at the potential negative influence of opioids, our results highlight that the impact of opioids varies by tumor type, suggesting a need for tumor-specific strategies in clinical practice [ 6 9 ]. The relationship between an ECOG PS of 1 or higher and reduced OS, elevated LDH levels above the normal range, and reduced PFS and OS suggests an association between increasing disease burden and OA usage, which may be related to a worse prognosis.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, OAs can disturb the composition of the intestinal microbiota and increase the presence of regulatory T cells (Tregs), resulting in impairment of the immune system. Retrospective cohort studies have indicated that the use of OAs may correlate with less favorable prognoses among patients treated with ICIs [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all solid tumors are sensitive to immunotherapy. The use of opioids is detrimental to survival outcomes for cancer patients receiving anti-PD-1/PD-L1 therapies ( 27 ). Two multicenter retrospective studies about solid cancers revealed that opioids used during immunotherapy were associated with a higher risk of early progression ( 28 , 29 ), and shorter OS ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the basic characteristics of the 23 included publications (10)(11)(12)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). These publications were from China (n=19), the United States of America (n=2), Australia (n=1), and France (n=1).…”
Section: Basic Characteristicsmentioning
confidence: 99%